Physical and mechanical properties of hydroxyapatite reinforced with 45S5 biocomposite - Alassan, Zarifah Nadakkavil (2016)
The physical and chemical properties of bioglass have significance in both fundamental and practical applications such as to be used in bone replacements and dental implants which included excellent osteoconductivity and bioactivity, ability to deliver cells and controllable biodegradability. Hydroxyapatite (HA), which has a similar structure as natural bone is prominent due to its biocompatibility and structure. However, it‘s not suitable to be used in load bearing applications due to the low mechanical strength. The introduction of the bioglass in the HA can helps to increase the mechanical strength of the HA so that it‘s able to be used in load bearing application. Melt quenching technique is used to synthesis 45S5 bioglass because it‘s simple, low cost and applicable in large scale industry. Hence, in this study, the physical and mechanical properties of HA, reinforced with sample glass (SG) and treated glass (TG) at different sintering temperatures have been studied. SG has been prepared by the conventional melt quenching technique with 45S5 type of bioglass composition using 45% SiO₂, 24.5% CaCO₃, 24.5% Na₂CO₃ and 6% P₂O₅ as the starting raw materials. Two series of HA reinforced with 45S5 bioglass were produced. The HASG samples were produced by mixing HA and SG according to their weight ratios and followed by pressing them into a pellet form. While, the HATG samples were produced by mixing HA with TG. Whereas, TG is SG sintered at 800 °C. All samples were sintered at 800, 1000, and 1200 °C with a soaking time of 3 hours. All samples under study were tested for density, XRD, FTIR, FESEM and microhardness. The density of SG decreases from 2.26 to 0.44 gcm-3 while molar volume increases from 34.99 to 179.36 cm3mol-1 as sintering temperature increased, which might be due to decomposition of carbonate group. Whereas, the density of HA increased from 1.99 to 3.11 gcm-3 with an increase in the sintering temperature and molar volume decreased from 252.03 to 162.30 cm3mol-1 with the sintering temperature. The density of both HASG and HATG samples was found decrease with an increase in the SG and TG. The density also decreased with the sintering temperature. The molar volume decreased with increasing in the composition of SG and TG, which also increased with temperature. This might be attributed to the replacement of low density SG with HA. The XRD results revealed amorphous phase of SG. After SG undergoes sintering process, the crystalline phase of sodium calcium silicate (Na₂Ca₃Si₆O₁₆), sodium, calcium phosphate (NaCaPO4) and quartz (SiO₂) was observed. It is evident from the study of HASG and HATG samples that SG behaves more as a sintering aid and promotes the conversion of HA to as –tetracalcium phosphate (β–TCP) and α–tetracalcium phosphate (α–TCP). The FTIR results revealed the presence of SiO4, PO4 vibrations in SG, HASG and HATG samples. In addition, the FESEM analysis revealed that by increasing the sintering temperature, the size of closed pores of SG samples increased, while the Ca/P ratio decreased. The FESEM morphology of the HASG and HATG samples showed irregular shapes of grains and closed pore formation. Smaller grain sizes and closed pores were observed in HATG samples. The incorporation of 45S5 bioglass in HA not only changes the crystal structure of HA but also introduced closed pores in the samples which caused the density and hardness reduced as well. This is due to decomposition of oxide material in the glass system. HA reinforced with 45S5 is suitable material for cancellous bone replacement, but the porosity of the sample not fulfilled the requirement for bone scaffold which is interconnected. Nearly, all the calculated Ca/P ratios were within a range for HA which is 1.3 to 2.0. Microvickers hardness of HASG and HATG increased with the sintering temperature and decreased as the composition of SG and TG is increased. This might be due to a coarser microstructure, crystal growth and porosity formation in the samples. Besides that, the hardness value in the range of 0.05–5.0 GPa shows that it's suitable used in cancellous bone applications. The compressive strength data of HATG were comparable to the cancellous bone which shows the compressive strength of 5–10 MPa.